Pelatihan pengolahan minyak jelantah menjadi sabun cuci untuk pemberdayaan ibu-ibu PKK di Bandar Lampung - Kusuma Handayani; Mohamad Kanedi; Salman Farisi; Wawan Abdullah S (Unri Conference Series: Community Engagement, 2020)
Minyak jelantah (mijel) is known in Indonesia as waste cooking oil. Even though it is a waste, mijel is still used by consumers for savings. The problem is, if it is used repeatedly more than three times, mijel can cause health problems. In addition to health hazards, if discharged through water channels, it can cause environmental pollution. Lack of public knowledge about the dangers of using the mijel in the end will have a negative impact. To educate the public about the health-risks of using mijel, we held a short training for housewives in Kelurahan Tanjung Agung, Bandar Lampung on July 22, 2020. This training provided the targeted housewives with the knowledge and skills to process the waste cooking oil into laundry soap. The purpose of this activity was to educate and provide training to the community, especially PKK women who interact directly with the use of mijel, about the dangers of mijel and how to manage it. PKK women who participated in the training seemed interested and understood the explanation described, this can be seen from the increase in the average pretest score from 55.7 to 81.3 at posttest. The benefits obtained by the participants are: 1) Understanding that using mijel more than three times can cause health problems for consumers. 2) Processing of waste cooking oil to laundry soap can reduce pollution in the aquatic environment.3) Laundry soap made from waste cooking oil can be a source of family income.